2005
DOI: 10.1038/sj.onc.1209239
|View full text |Cite
|
Sign up to set email alerts
|

DDX3, a DEAD box RNA helicase, is deregulated in hepatitis virus-associated hepatocellular carcinoma and is involved in cell growth control

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer deaths worldwide and is highly correlated with hepatitis virus infection. Our previous report shows that a DEAD box RNA helicase, DDX3, is targeted and regulated by hepatitis C virus (HCV) core protein, which implicates the involvement of DDX3 in HCV-related HCC development. In this study, the potential role of DDX3 in hepatocarcinogenesis is investigated by examining its expression in surgically excised human HCC specimens. Here we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
146
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 76 publications
3
146
4
Order By: Relevance
“…Presumably, the biological roles of DDX3 may overlap with other eIF4E-binding proteins to provide a backup or compensatory mechanism. As shown in our recent work, DDX3 exerts an inhibitory effect on cell growth, whereas a genetic knockdown of DDX3 results in an enhancement of cell proliferation (Chang et al, 2006;Chao et al, 2006). This cell growth-suppressive property of DDX3 is linked to its transactivation ability on p21 waf1/cip1 promoter through physical interaction with Sp1 (Chao et al, 2006).…”
Section: Ddx3 Interacts With Eif4e and Regulates Translationmentioning
confidence: 57%
See 4 more Smart Citations
“…Presumably, the biological roles of DDX3 may overlap with other eIF4E-binding proteins to provide a backup or compensatory mechanism. As shown in our recent work, DDX3 exerts an inhibitory effect on cell growth, whereas a genetic knockdown of DDX3 results in an enhancement of cell proliferation (Chang et al, 2006;Chao et al, 2006). This cell growth-suppressive property of DDX3 is linked to its transactivation ability on p21 waf1/cip1 promoter through physical interaction with Sp1 (Chao et al, 2006).…”
Section: Ddx3 Interacts With Eif4e and Regulates Translationmentioning
confidence: 57%
“…The DDX3-eIF4E interaction is required for the tumor growth suppressive ability of DDX3 Our previous studies have demonstrated that the DDX3-mediated upregulation of p21 waf1/cip1 promoter activity could account for the tumor suppressor function of DDX3 (Chang et al, 2006;Chao et al, 2006). Based on this, we extended our studies to address whether the DDX3-eIF4E interaction is required for the aforementioned property of DDX3.…”
Section: Gakdyrqssg Ag-ssfgssr Ggrs----sg Hggsr----------gfggg -Yggfymentioning
confidence: 72%
See 3 more Smart Citations